PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIc SMP TELEKOMUNIKASI PEKANBARU - ', Nurlaily; Heleni, Susda; ', Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is background based on mathematics learning outcomes in class VIIIc students of SMP Telekomunikasi Pekanbaru which is still under Minimum Criteria of mastery learning that has been settled by the school that is 75. This type of research is the classroom action research with 2 cycles. The subject in this research were 16 male students and 12 female students with heterogeneous ability. The aims of this research are to improve the learning process and improve student’s mathematics learning outcomes in class VIIIc of SMP Telekomunikasi Pekanbaru in odd semester of the 2016/2017 academic year based on KD 1.3 Understanding relations and functions and on KD 1.4 Determining the value of the function. This research was conducted on August 29, 2016 until 21 September 2016. The data in research were obtained from the observations of teacher and student activity and student outcomes by analyzing qualitatively and quantitatively. Based on the data analysis of teacher and student activity after applying the cooperative learning model of Think Pair Square Structural Approach, teacher and student activities have done well and had an improvement at each meeting. Based on the data analysis of student learning outcomes, there is an improve in student learning outcomes in each cycle. Based on the analysis of KKM achievement, there were 12 students who reached KKM at UH 1 with percentage 42.85% and and 16 students at UH II with percentage of 57.14%. Based on the result of research show that, there is an improve of students who get very high criteria and the decrease of students who get enough and low criteria. From this research it can be concluded that the implementation model of Think Pair Square structural approach can improve the learning process and also to improve student’s of mathematics learning outcomes in class VIIIc of SMP Telekomunikasi Pekanbaru.Key words: Mathematics learning outcome, Cooperative learning, Think Pair Square,Classaction research